3-Pentylcatechol, a Non-Allergenic Urushiol Derivative, Displays Anti-Helicobacter pylori Activity In Vivo - Hang Yeon Jeong; Tae Ho Lee; Ju Gyeong Kim; Sueun Lee; Changjong Moon; Xuan Trong Truong; Tae-Il Jeon; Jae-Hak Moon (MDPI AG, 2020)
We previously reported that 3-pentylcatechol (PC), a synthetic non-allergenic urushiol derivative, inhibited the growth of Helicobacter pylori in an in vitro assay using nutrient agar and broth. In this study, we aimed to investigate the in vivo antimicrobial activity of PC against H. pylori growing in the stomach mucous membrane. Four-week-old male C57BL/6 mice (n = 4) were orally inoculated with H. pylori Sydney Strain-1 (SS-1) for 8 weeks. Thereafter, the mice received PC (1, 5, and 15 mg/kg) and triple therapy (omeprazole, 0.7 mg/kg; metronidazole, 16.7 mg/kg; clarithromycin, 16.7 mg/kg, reference groups) once daily for 10 days. Infiltration of inflammatory cells in gastric tissue was greater in the H. pylori-infected group compared with the control group and lower in both the triple therapy- and PC-treated groups. In addition, upregulation of cytokine mRNA was reversed after infection, upon administration of triple therapy and PC. Interestingly, PC was more effective than triple therapy at all doses, even at 1/15th the dose of triple therapy. In addition, PC demonstrated synergism with triple therapy, even at low concentrations. The results suggest that PC may be more effective against H. pylori than established antibiotics.